Evidence of Biparental Mitochondrial Inheritance from Self-Fertile Crosses between Closely Related Species of Ceratocystis - Daniella van der Walt; Emma T. Steenkamp; Brenda D. Wingfield; P. Markus Wilken (Journal of Fungi, 2023)
Hybridization is recognized as a notable driver of evolution and adaptation, which closely related species may exploit in the form of incomplete reproductive barriers. Three closely related species of Ceratocystis (i.e., C. fimbriata, C. manginecans and C. eucalypticola) have previously been shown to hybridize. In such studies, naturally occurring self-sterile strains were mated with an unusual laboratory-generated sterile isolate type, which could have impacted conclusions regarding the prevalence of hybridization and inheritance of mitochondria. In the current study, we investigated whether interspecific crosses between fertile isolates of these three species are possible and, if so, how mitochondria are inherited by the progeny. For this purpose, a PCR-RFLP method and a mitochondrial DNA-specific PCR technique were custom-made. These were applied in a novel approach of typing complete ascospore drops collected from the fruiting bodies in each cross to distinguish between self-fertilizations and potential hybridization. These markers showed hybridization between C. fimbriata and C. eucalypticola and between C. fimbriata and C. manginecans, while no hybridization was detected in the crosses involving C. manginecans and C. eucalypticola. In both sets of hybrid progeny, we detected biparental inheritance of mitochondria. This study was the first to successfully produce hybrids from a cross involving self-fertile isolates of Ceratocystis and also provided the first direct evidence of biparental mitochondrial inheritance in the Ceratocystidaceae. This work lays the foundation for further research focused on investigating the role of hybridization in the speciation of Ceratocystis species and if mitochondrial conflict could have influenced the process.